L’humanisme juridique de Louis Le Caron d’après son « Commentaire sur l’edict des secondes nopces » (1560) - Lombart, Nicolas (AMU Press, 2011)
The aim of this paper is to show the deep relationship between the second marriage as a juridical and political problem in France in 1560 and the critical method of the « juridical humanism » used by Le Caron, based on the desacralization of the Roman law (by using philosophical and historical references) and the glorification of the French language and civilization. In that extent, the Commentaire sur l’edict des secondes nopces (1560) may be seen as an exercise of « illustration » of the French juridical language (refering to the literary context of the marriage) and praise of the king of France (paterfamilias and lawgiver).